2015
DOI: 10.1002/cyto.a.22619
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric analysis of the graft‐versus‐Leukemia‐Effect After Hematopoietic Stem Cell Transplantation in Mice

Abstract: Acute Graft-versus-Host-Disease (aGvHD) is one of the major complications following allogeneic hematopoietic stem cell transplantation (HSCT). Although rather helpful, the use of conventional immunosuppressive drugs leads to general immunosuppression and is toxic. The effects of CD41 T-cells, in respect to the development of aGvHD, can be altered by administration of antihuman CD4 monoclonal antibodies, here MAX.16H5 IgG 1 . This approach must be tested for possible interference with the Graft-versus-Leukemia-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…In previous work, our data showed that the short-term ex vivo incubation of an allogeneic graft with the non-depleting anti-human CD4 antibody MAX.16H5 IgG 1 (murine) led to a significant GVHD reduction without negatively influencing the induced GVL effect ( 26 ). Additionally, NOD.Cg-Prkdc scid IL-2rg tm1Wjl /SzJ (NSG) recipient mice showed a significantly increased survival after xenogeneic transplantation of human peripheral blood mononuclear cells when the graft was pre-treated with the anti-human CD4 antibody MAX.16H5 IgG 1 ex vivo ( 27 ).…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations
“…In previous work, our data showed that the short-term ex vivo incubation of an allogeneic graft with the non-depleting anti-human CD4 antibody MAX.16H5 IgG 1 (murine) led to a significant GVHD reduction without negatively influencing the induced GVL effect ( 26 ). Additionally, NOD.Cg-Prkdc scid IL-2rg tm1Wjl /SzJ (NSG) recipient mice showed a significantly increased survival after xenogeneic transplantation of human peripheral blood mononuclear cells when the graft was pre-treated with the anti-human CD4 antibody MAX.16H5 IgG 1 ex vivo ( 27 ).…”
Section: Introductionmentioning
confidence: 80%
“…Bone marrow cells (BMCs) and splenocytes (SpC) were dissected from CD4/DR3 mice as previously described ( 26 ). BMCs and splenocytes were either incubated with 800 μg MAX.16H5 IgG 1 (1mg/mL, Biotest) per 1.4 × 10 8 cells or without antibody.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Graft‐versus‐host‐disease (GvHD) is a feared, often lethal complication following hematopoietic stem cell transplantation. Schmidt et al demonstrated last year in a mouse model that GvHD of transplanted murine T‐helper cells can be prevented by administration of anti‐human CD4 monoclonal antibodies . As mice can lie, the authors (Hilger et al, this issue, page 803) expanded their experiments by transplanting human leukocytes into another mouse model.…”
mentioning
confidence: 99%